Comportamento de estacas broca compostas de solo-cimento e resíduo de beneficiamento de pedras preciosas a partir de provas de carga estática - Edler, Patrícia (2011)
In civil constructions after the digging process it is common to have soil as a residue. This material sometimes is put in inadequate places which can have environmental problems and high cost. The same occurs with the processes of beneficiation of precious stones, which also generate waste that need solutions. The utilization of residues and by-products on civil constructions may be an excellent alternative to decrease the environmental impact and to help the sustainable development. This work has as main objective to evaluate the possibility of use of soil, residues from precious stones and Portland cement in bored piles. Initially, a mixture was developed with the materials that would form the piles. The mixture presenting the best strength characteristics was the one with 50% of residues and 50% of soil, containing 10% of Portland cement. Three bored piles (twenty-three centimeters of diameter and three meters of depth) with the found mixture were used during the field tests. The results obtained were compared to the results of concrete pile. It was observed that stabilized mixture pile has the same load capacity as the pile made of traditional concrete. It was possible to conclude that the use of the mixture of soil, residues and Portland cement is technically viable and, after the cost analysis, it was verified that final price of a bored pile made of the mixture mentioned, may be up to 38% cheaper than one made with traditional concrete